RELEVANSI KURIKULUM PERBANKAN SYARI’AH DENGAN DUNIA KERJA (Analisis Kurikulum Program Studi Perbankan Syari’ah STAIN Sultan Qaimuddin Kendari) - Akmal, Akmal (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2014)
Analysis of curriculum study program of STAIN Kendari Islamic banking to its relevance to the world of work insustri sharia compliance with the industrial market pragmatism sharia. The composition and structure of the study program curriculum is designed on Islamic banking filosafi "Bee Smart" which comprises: main course competencies (MKU) 56%, 21% charged basic subjects (MKD), 12% of subjects supporting the rest of MKL. Semester credit units (credits) to be solved Islamic banking department of student totaled 145 credits consisting of 28 credits MKD, MKU 93 credits, 18 credits MKP, MKL, 12 credits. Learning tool is equipped with a technology-based instructional media and completeness of lab planning and mini sharia banks. SDM is supported 37 faculty lecturer sharia and Islamic economics, 6 lecturers Prodi with sharia-based educational qualifications, which amount will be increased to 16 lecturers in 2019.Constraints Prodi Islamic banking is a common obstacle that opens PTAI department / department of banking / economy sharia with the nomenclature of which the HR people and the implementation of the curriculum tend to charge Fiqh Muamalat concepts and theories. While the industrial market pragmatism requires the implementation of sharia more technical curriculum, the Faculty of Economics and Business nomenclature Islam is more appropriate, such as the status of the plan over STAIN be IAIN Sultan Qaimuddin Kendari nomenclature Faculty of Economics and Business Islamic adjusted.Keywords: Curriculum, Prodi Islamic banking, shariah industry workforce.